Quinton Holder: capstone - Holder, Quinton, artist (Colorado State University. Libraries, 2023)
The artist's statement: My name is Quinn Holder and I am a 28-year-old artist with a Bachelor of Fine Arts degree with a Graphic Design concentration from Colorado State University, as well as a previous Associate of Fine Arts degree with a concentration in Painting. I grew up here in Fort Collins and have lived here my entire life with no real plans on leaving the area. Through my strong background in painting and color theory, my recent graphic design studies have gone very smoothly. I have more than 10 years worth of creative experience under my belt, so my portfolio of work is very broad. I enjoy web building, logo design, graphic and media production, and producing works that both myself and others can interact with in positive ways. A few things I enjoy in my free time aside from creative work are spending time with the people I care about, skateboarding with my friends, playing video games, and continuing to build and work on my ever expanding skill set. Even if my work isn't your particular cup of tea, I hope my work inspires you and others and can potentially spark a conversation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design